V-Pharmel performance management case - Varma, Arup; Budhwar, Pawan S. ([London] : SAGE, 2016)
We are presented with a company's management trainee (MT) scheme. V-Pharmel is an integrated consumer products company with an ethical values-based leadership model. Their two-year training program offers the opportunity to graduates from top US business schools to work with the company while getting expertise in a field. At the end they are to receive an evaluation report based on their performance. The case focuses on the evaluation experience of the only international student of the program, AJ.
Originally Published in: Harzing, A. W., & Pinnington, A. (2011). V-Pharmel Performance Management Case. In international human resource management (3rd ed., pp. 460-463). London: SAGE Publications Ltd. Print. ISBN: 9781847872937.
Description based on online resource; title from home page (viewed on April 21, 2016).
Keywords: elektronické knihy; electronic books; Employees -- Rating of -- Case studies; Employees -- Training of -- Case studies